Species diversity and abundance of resident and migratory birds in urban parks of San José, Costa Rica (UNED Research Journal, 2018)
With the exception of a few large cities, there is little knowledge about the urban birds of Latin America. I used linear transects in 15 urban parks in San José city between September and December, 2009 and found 40 species, mostly Tyrannidae (n=10) and Parulidae (n=9). There were 23 residents (mostly Tyrannidae), 15 northern migrants (mostly Parulidae) and one southern migrant. The most representative species were Contopus sp. and Setophaga petechia. Zenaida asiatica, Turdus grayi, and Quiscalus mexicanus were widespread, as was the pigeon, Columba livia, which could reach 122 individuals per park. Diversity and abundance were determined by park size, the complexity of vegetation and the proximity to vegetation fragments. The urban parks are being used as passing and permanent areas by the migratory birds and the biophysical characteristics of some parks favor Columba livia and Quiscalus mexicanus, generating competition, predation and displacement of another species, as well as infrastructure damage. These green areas could be used for bird watching and education
Keywords: Urban park; green areas; urban ecology; urban biodiversity; resident birds; migratory birds